Effect of Surface States on Joining Mechanisms and Mechanical Properties of Aluminum Alloy (A5052) and Polyethylene Terephthalate (PET) by Dissimilar Friction Spot Welding - Yusof, F.; Muhamad, M.R.; Moshwan, R.; Jamaludin, M.F.; Miyashita, Y. (MDPI, 2016)
In this research, polyethylene terephthalate (PET), as a high-density thermoplastic sheet, and Aluminum A5052, as a metal with seven distinct surface roughnesses, were joined by friction spot welding (FSW). The effect of A5052’s various surface states on the welding joining mechanism and mechanical properties were investigated. Friction spot welding was successfully applied for the dissimilar joining of PET thermoplastics and aluminum alloy A5052. During FSW, the PET near the joining interface softened, partially melted and adhered to the A5052 joining surface. The melted PET evaporated to form bubbles near the joining interface and cooled, forming hollows. The bubbles have two opposite effects: its presence at the joining interface prevent PET from contacting with A5052, while bubbles or hollows are crack origins that induce crack paths which degrade the joining strength. On the other hand, the bubbles’ flow pushed the softened PET into irregularities on the roughened surface to form mechanical interlocking, which significantly improved the strength. The tensile-shear failure load for an as-received surface (0.31μm Ra) specimen was about 0.4-0.8 kN while that for the treated surface (>0.31μm Ra) specimen was about 4.8-5.2 kN.